LITERACY AND LITERACY - Araújo da Costa, Marluce; de Cáscia da Costa, Francisca; Dias Costa, Cleide; Cristina Medeiros de Azevedo Silva, Ana; Amilton da Costa, José; Medeiros, Salésia (Revista Gênero e Interdisciplinaridade, 2025)
The topic of literacy, a very current one in the Brazilian context, has not always been clearly understood by elementary school teachers, in the early years responsible for helping children learn to read and write. Therefore, this article consists of a theoretical reflection on this process, aiming to clarify and deepen its understanding through a bibliographic review based on the contributions of several renowned authors. Initially, the article seeks to understand the different aspects related to the topic that has changed the meaning and importance of literacy in schools; it also emphasizes the definition, etymology, and the distinction between literacy and literacy. It also addresses the various types or modalities; the possible relationships between literacy and schooling; the challenges and implications of literacy for education, specifically literacy practices.